Bone and joint infections: clinical forms, risk factors, prevention, etiology, diagnosis and treatment - Malmur, Paweł Arkadiusz; Romanowska, Aleksandra; Biaduń-Mućko, Weronika; Rogowska-Borettini, Kinga; Padkowska, Aleksandra; Pieniążek, Jakub Maciej; Arciszewska, Klaudia; Dobosz, Mateusz (Journal of Education, Health and Sport, 2026)
Bone and joint infections pose many threats to human life and health. The scope of knowledge and skills to deal with this problem has improved significantly in recent years. The chosen direction should be continued so that we can prevent and treat bone and joint infections with the highest possible effectiveness.